Winged scapula following axillary thoracotomy with long thoracic nerve preservation. Issue 2 (19th February 2020) - Isono, Tomomi; Mori, Shigeshi; Kusumoto, Hidenori; Shiono, Hiroyuki
Abstract : Winged scapula is a rare condition caused by injuries to the long thoracic nerve (LTN) and accessory nerves. A 69-year-old man underwent surgery for right lung cancer. Video-assisted thoracic surgery was converted to axillary thoracotomy at the fourth intercostal space. The latissimus dorsi was protected, and the serratus anterior was divided on the side anterior to the LTN. Two months after discharge, he presented with difficulty in elevating his right arm and protrusion of the scapula from his back. Active forward flexion of the right shoulder was limited to 110° and abduction to 130°. He was diagnosed with winged scapula. After 6 months of occupational therapy, the symptoms improved. The LTN may have been overstretched or damaged by the electric scalpel. We recommend an increased awareness of the LTN, and to divide the serratus anterior at a site as far as possible from the LTN to avoid postoperative winged scapula.